Photovoltaic/Thermal (PV/T) Systems Principles, Design, and Applications - Al-Waeli, Ali H. A.; Kazem, Hussein A.; Chaichan, Miqdam Tariq; Sopian, Kamaruzzaman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides the most up-to-date information on hybrid solar cell and solar thermal collectors, which are commonly referred to as Photovoltaic/Thermal (PV/T) systems. PV/T systems convert solar radiation into thermal and electrical energy to produce electricity, utilize more of the solar spectrum, and save space by combining the two structures to cover lesser area than two systems separately. Research in this area is growing rapidly and is highlighted within this book. The most current methods and techniques available to aid in overall efficiency, reduce cost and improve modeling and system maintenance are all covered. In-depth chapters present the background and basic principles of the technology along with a detailed review of the most current literature. Moreover, the book details design criteria for PV/T systems including residential, commercial, and industrial applications. Provides an objective and decisive source for the supporters of green and renewable source of energy Discusses and evaluates state-of-the-art PV/T system designs Proposes and recommends potential designs for future research on this topic.
Introduction -- PV/T design principles -- Advances in PV/T systems -- PV/T system feasibility in world deserts -- Environmental conditions and its effect on PV/T performance -- Applications of PV/T systems.
Keywords: Materials; Catalysis; Force and energy; Renewable energy sources; Electric power production; Materials for Energy and Catalysis; Renewable Energy; Electrical Power Engineering; Mechanical Power Engineering